2016
DOI: 10.1182/blood-2016-06-723205
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplantation cyclophosphamide and sirolimus for prevention of GVHD after HLA-matched PBSC transplantation

Abstract: Graft-versus-host disease (GVHD), both acute and chronic, is still a leading cause of nonrelapse mortality after transplantation. 1 Highdose, posttransplantation cyclophosphamide (PTCy) is an attractive approach for in vivo allodepletion across the HLA barrier in allogeneic hematopoietic stem cell transplantation (HSCT), aimed at inducing a state of immunologic tolerance and preventing GVHD.2 This clinical platform was demonstrated first in the reduced-intensity conditioning, haploidentical allogeneic HSCT set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 24 publications
3
35
1
Order By: Relevance
“…Solomon et al, using sirolimus in addition to PTC, reported an incidence of acute GVHD grades II to IV, acute GVHD grades III and IV, and chronic GVHD of 46%, 15%, and 31%, respectively [21]. A similar study with shorter follow-up examining the combination of PTC, sirolimus, and, in patients receiving grafts from unrelated donors, MMF, reported incidences of acute GVHD grades II to IV, acute GVHD grades III and IV, and chronic GVHD of 23%, 4%, and 13%, respectively [22]. Although these results seem favorable, the re-addition of calcineurin and mTOR inhibitors to PTC potentially hinders several benefits of PTC.…”
Section: Discussionmentioning
confidence: 96%
“…Solomon et al, using sirolimus in addition to PTC, reported an incidence of acute GVHD grades II to IV, acute GVHD grades III and IV, and chronic GVHD of 46%, 15%, and 31%, respectively [21]. A similar study with shorter follow-up examining the combination of PTC, sirolimus, and, in patients receiving grafts from unrelated donors, MMF, reported incidences of acute GVHD grades II to IV, acute GVHD grades III and IV, and chronic GVHD of 23%, 4%, and 13%, respectively [22]. Although these results seem favorable, the re-addition of calcineurin and mTOR inhibitors to PTC potentially hinders several benefits of PTC.…”
Section: Discussionmentioning
confidence: 96%
“…Post-transplant cyclophosphamide (PTCY) has been used both in the setting of sibling donor transplants and haploidentical transplants and has been shown to be associated with a low incidence of acute and chronic GVHD [7][8][9][10]. We undertook a prospective, phase II, single-arm study to evaluate the utility of PTCY as the sole GVHD prophylaxis in patients with SAA undergoing sibling donor HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…MMF was added to the regimen in patients receiving MUD transplants. The incidence of grades II-IV acute and cGvHD seemed better at 23 and 13% (36).…”
Section: Ptcy and Cni Or Mtor Inhibitors In Mrd And Mud Transplantmentioning
confidence: 90%